Retrospective review of facial nerve schwannomas: the Universiti Kebangsaan Malaysia Medical Centre experience - Mazita A; Zahirrudin Z; Saim L; Asma A (Penerbit UKM, 2010)
Facial nerve schwannoma is a rare slow growing benign tumour which arises from the Schwann cell of the neurilemma. A retrospective review of 6 patients who had been diagnosed with facial nerve schwannoma between 1998 and 2008 was conducted. There was equal distribution of male and female patients. The mean age was 42 years (range 19 to 66 years). The tumour originated in the internal auditory canal (2 patients), intra-temporal (3 patients) and intraparotid (1 patient) segments of the facial nerve. All tumours were successfully removed and facial nerve continuity was pre-served in 2 cases. The presenting symptoms of facial nerve schwannoma are non specific and dependent on the site of tumour origin. It is a great mimicker of other lesions that can present at the same location. The surgeon should have a high index of suspicion when patients present with progressive facial nerve palsy. Patients should always be counselled regarding risk of facial paralysis because the diagnosis of facial nerve schwannoma is often confirmed intra-operatively.